GOOD OUTCOMES OF OCULAR MYASTHENIA GRAVIS IN A YOUNG ADULT MALE: A CASE REPORT: Poster Presentation - Case Report - Resident - Muhammad Wahyu Aghdhi Pradipta; Lukisiari Agustini (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Myasthenia gravis (MG) is characterized by fluctuating weakening and fatigability of skeletal muscles. Ocular MG (OMG) occurs when the symptoms of MG are limited to the ocular muscles. Case Illustration : A 21-year-old male presents with a two-month history of drooping both eyelids. The drooping eyelids improved in the morning or after a nap, and got worse in the evening. Ocular examination revealed limitation towards all gazes with bilateral ptosis. Visual acuity, anterior segment, visual fields, slit lamp, and fundus examinations were unremarkable. The ice pack and rest test resulted in a significant improvement after two minutes of ice pack application and 30-minute rest, raising suspicion for the diagnosis of MG. Acetylcholine receptor antibody (AChR) test was positive for AChR binding antibody. Treatment for OMG is initiated with an oral acetylcholinesterase inhibitor, pyridostigmine, and corticosteroid. The ptosis and ophthalmoplegia improved after one week follow- up and recovered completely after eight weeks of follow-up. Discussion : The hallmarks of MG are fluctuating fatigable muscle weakness that worsen with activity and improve on rest. Neurological exam and clinical neurological history are essential to establish the diagnosis. Bedsite tests, electrophysiologic test, and the antibody test all support the clinical diagnosis of MG. Conclusion : OMG progresses to its generalized form 90% of the time during the first two years of the onset of ocular symptoms. Early detection and prompt treatment are the key which may help to prevent or minimize the occurrence of myasthenia crisis.